OP11 Service evaluation of the hepatocellular carcinoma ultrasound surveillance programme in South Wales. (20th September 2022) - Yassen, Lava; Ball, Belinda; Hams, Pam; Andrews, Angela; Samuel, Rebecca; Neville, Peter; Lee, Bee; Gothegal, Gireesh; Yates, Alison; Samuel, David
Abstract : Hepatocellular Carcinoma (HCC) 6-monthly ultrasound surveillance in patients with cirrhosis is recommended by multiple international liver associations. The changing at-risk population of HCC and lack of UK data warrants review of its effectiveness. A retrospective study of patients diagnosed with HCC between March 2019 and March 2022 across 2 sites in the Cwm Taf Morgannwg health board was performed. Patient demographics, aetiology of underlying cirrhosis and if the HCC was diagnosed through surveillance was documented. Tumour characteristics, alpha-fetoprotein (AFP) levels and Barcelona Clinic Liver Cancer (BCLC) staging at the time of diagnosis was noted. Treatment receipt, including curative or palliative intent, outcomes and survival were also recorded. Data from 68 patients with HCC was analysed. Cirrhosis was present in 78.5% patients with HCC. Non-alcoholic fatty liver disease (NAFLD) was the most frequent aetiology of cirrhosis (50%). 22.1% patients were diagnosed via the surveillance programme with 28.6% of these patients diagnosed at BCLC stages 0-A compared to 5.9% in the non-surveillance group (p=0.04). The size of the patients' largest tumours were significantly smaller in the surveillance compared to the non-surveillance group (p=5.7 x10 6 ). 49.2% patients had abnormal AFP levels (>20 ng/mL) at diagnosis with 13.3% patients in the surveillance group diagnosed on suspicion of their abnormal AFP levels. 38.5% patients with HCC diagnosed on surveillance were treated initially with curative intent in comparison to 7.8% in the non-surveillance group (p=0.04). However, survival time between these patients was not statistically significant. We have demonstrated that the HCC ultrasound surveillance programme for cirrhotic patients in South Wales is associated with early-stage tumour detection and curative therapy receipt.